Carcinomatous pleuritis in women with malignant tumors of reproductive system: potentialities of a cytological technigue - O. G. Grigoruk; A. F. Lazarev; L. M. Bazulina; M. N. Chechulin (Бюллетень сибирской медицины, 2009)
А cytological technique to determine the character of pleura pathology with malignant tumors among 297 women was used. The features of malignant cells of tumors of reproductive system in pleurisies with breast carcinoma (119), ovarian (73) and endometrial carcinoma (4) were studied. A light microscopy, also immunocytochemical technique with a set of 2—14 antibodies in difficult cases for diagnostics was used. With the dissemination of breast carcinoma on pleura, the specific pathogonomic characters in 78.2 % of cases are found. With ovarian carcinoma according to the certain cytological features also taking into consideration immunocytological characters in 34, 2% of observations, the site of primary tumor was exactly revealed. Indirect characters were noticed in 61, 6% of cases. With endometrial carcinoma, the special specific characters were not observed. Immunocytochemical technique can play a critical role in a differential diagnose of canceromatous pleurisies.